2015
DOI: 10.1111/vsu.12327
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized Comparison of the Effect of Two Antimicrobial Regimes on Surgical Site Infection Rate in Dogs Undergoing Orthopedic Implant Surgery

Abstract: SSI rates in this population of dogs were similar where antimicrobial prophylaxis was administered perioperatively over 3 hours or as a course continued for 6 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 31 publications
0
48
2
3
Order By: Relevance
“…Contradictory findings, however, have been reported. Several reports of recent studies involving dogs undergoing TPLO have described a reduced risk of postoperative infection with the use of postoperative antibiotic therapy, while other reports have described findings that postoperative antibiotic therapy did not result in a significant reduction in SSI . However, the only two studies in which dogs weighing >50 kg were assessed provided evidence of a protective effect of the use of postoperative antimicrobial treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory findings, however, have been reported. Several reports of recent studies involving dogs undergoing TPLO have described a reduced risk of postoperative infection with the use of postoperative antibiotic therapy, while other reports have described findings that postoperative antibiotic therapy did not result in a significant reduction in SSI . However, the only two studies in which dogs weighing >50 kg were assessed provided evidence of a protective effect of the use of postoperative antimicrobial treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that the infection risk increases with the duration of surgery, including clean and clean‐contaminated wounds among dogs having orthopedic, minimally invasive, or open surgery . In horses, the risk increases with nonclean surgical sites, implants, and standing procedures as well as with arthroscopy with large subchondral bone lesions (>40 mm) or long abdominal incisions (>27 cm) . In cattle, SSI risk has also been shown to increase with increasing wound contamination (with the lowest incidence associated with clean and the highest reported for dirty wounds) .…”
Section: Managing Risks Associated With Surgical Site Infectionsmentioning
confidence: 99%
“…A recent randomized clinical trial found that the use of postoperative oral cephalexin or potentiated amoxicillin for 7 days reduced the infection risk among dogs undergoing a clean orthopedic surgery requiring plate fixation . However, some have found no difference in SSI rates among dogs undergoing clean orthopedic surgeries with and without antimicrobial therapy, and others have found similar joint infection rates among horses undergoing elective arthroscopy without the use of antimicrobial drugs compared with historical reports when AMD were used . Although there is debate regarding the use of prophylaxis, these findings suggest that this practice should be considered on a case by case basis, especially if the patient has other risk factors for the development of an SSI.…”
Section: Prevention Of Surgical Site Infectionsmentioning
confidence: 99%
“…There is also no evidence that prolonged treatment will reduce surgical site infections in clean surgeries, even when implants are placed (Aiken et al . ). The authors believe that a first‐line antimicrobial such as penicillin or oxtetracycline should be used in such cases, thus reserving an important and protected antimicrobial for those cases which satisfy criteria for its use (Bowen ).…”
mentioning
confidence: 97%
“…To date, there is no evidence that the risk of surgical site infection is increased with standing surgery, as compared with surgery performed under general anaesthesia, although antimicrobial provision is not detailed in the case series described by Payne and Compston (2012). There is also no evidence that prolonged treatment will reduce surgical site infections in clean surgeries, even when implants are placed (Aiken et al 2015). The authors believe that a first-line antimicrobial such as penicillin or oxtetracycline should be used in such cases, thus reserving an important and protected antimicrobial for those cases which satisfy criteria for its use (Bowen 2013).…”
mentioning
confidence: 99%